2003
DOI: 10.1021/jf0304223
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant Effects of the Limonoids from Entandrophragma candolei (Meliaceae) on the Gram Pod Borer, Helicoverpa armigera (Lepidoptera:  Noctuidae)

Abstract: The biological activity of the limonoids prieurianin and epoxyprieurianin isolated from Entandrophragma candolei (Harms) (Meliaceae) and their respective acetates was assessed using the gram pod borer, Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae). The compounds exhibited strong antifeedant activity in a diet choice bioassay with epoxyprieurianin acetate being most effective with 48.3 ppm deterring feeding by 50% (DI50) and prieurianin the least effective (DI50 = 91.4 ppm). The effect on growth of lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 19 publications
3
47
0
Order By: Relevance
“…A PP2A was recently demonstrated to be involved in apical/basal PM localization of PIN auxin transporters (21); thus, the identification of cantheridin as affecting RIP-GFP localization provided validation our screening approach. Another compound that was active in our assay in the low micromolar range was reported as prieurianin, a limonoid displaying ecdysone antagonist and anti-feedant activity in insects (22,23); however, we propose the name endosidin1 (ES1), which is descriptive of its cellular mode of action. Related limonoids were without effect indicating the selectivity of the screen for ES1 (Table S1).…”
Section: Resultsmentioning
confidence: 92%
“…A PP2A was recently demonstrated to be involved in apical/basal PM localization of PIN auxin transporters (21); thus, the identification of cantheridin as affecting RIP-GFP localization provided validation our screening approach. Another compound that was active in our assay in the low micromolar range was reported as prieurianin, a limonoid displaying ecdysone antagonist and anti-feedant activity in insects (22,23); however, we propose the name endosidin1 (ES1), which is descriptive of its cellular mode of action. Related limonoids were without effect indicating the selectivity of the screen for ES1 (Table S1).…”
Section: Resultsmentioning
confidence: 92%
“…This behavior has also been observed by others (Mordue (Luntz) and Blackwell, 1993;Coelho et al, 2007;Ramos et al, 2009). A drop in ECI indicates that more food is being metabolized for energy and less is being converted to body mass, i.e., growth of insect (Koul et al, 2003). ECD also decreases as the proportion of digested food metabolized for energy increases (Wheeler and Isman, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…3,23,24) Azadirachtin and related limonoids from neem tree have shown strong antifeedant and growth regulating activity and at the same time these compounds are highly bio-degradable, are very slightly toxic towards non-target organisms, while they are non-toxic towards humans and mammals in general, with very low persistence in systemic action, 21,25) this is the reason why an array of insecticides and pesticides comprising of azadirachtin as principal constituent and based on neem extract are available today in the market. Koul et al 26,27) have further shown that azadirachtin being the most active compound in neem is not synergized or influenced by any other limonoid, but other non-azadirachtin limonoids show synergism in specific combination, which may be due to their different modes of action.…”
Section: Activities On Insectsmentioning
confidence: 99%